2011
DOI: 10.1111/j.1365-2028.2010.01252.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of river geomorphologic features on hippopotamus density distribution along the Luangwa River, Zambia

Abstract: River geomorphologic features along a 165-km stretch of the Luangwa River in eastern Zambia were assessed in 2008 to determine their influence on hippopotamus pattern of density distribution. A fixed high wing Cessna 206 aircraft fitted with geographical positioning system (GPS) was flown over the stretch taking coordinates for each geomorphologic feature, followed by taking length in metres of each geomorphologic feature on the ground. A total hippopotamus count was later carried out along the same stretch. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 3 publications
1
27
0
Order By: Relevance
“…The number and nature of geomorphologic features (river bends, confluences and lagoons) was still 64 and had not changed since Chansa and others carried out a similar study [5] [6] reported in 2011. After food (grass biomass), geomorphologic features were the second most important factor in regulating hippo pattern of population density distribution between study blocks A-H along the 165 km stretch of the Luangwa River and not security.…”
Section: Prevalence Of River Geomorphologic and Security Featuresmentioning
confidence: 78%
See 3 more Smart Citations
“…The number and nature of geomorphologic features (river bends, confluences and lagoons) was still 64 and had not changed since Chansa and others carried out a similar study [5] [6] reported in 2011. After food (grass biomass), geomorphologic features were the second most important factor in regulating hippo pattern of population density distribution between study blocks A-H along the 165 km stretch of the Luangwa River and not security.…”
Section: Prevalence Of River Geomorphologic and Security Featuresmentioning
confidence: 78%
“…A table showing study blocks, total number of geomorphologic features and their mean length and width measurements per study block and hippopotamus population density which was earlier presented by Chansa and others [5] was also verified. An F Test described by Dytham [11] and Fowler and others [12], was used to compare the means of population density between the upper and lower blocks.…”
Section: River Geomorphologymentioning
confidence: 99%
See 2 more Smart Citations
“…The hippopotamus retracted into lagoons and upper reaches and only returned to the main channel in the dry season. Attwell (1963) and Chansa et al (2011) also noted that areas with river meanders and extensive grasslands with palatable grass species such as Cynodon dactylon would carry high densities. Attwell (1963) further gave an example of the Lufupa River a tributary of the Kafue River particularly in respect of its upper reaches where the hippopotamus populations were higher than the main Kafue River on account of the slow water flow and increased amount of flood plain habitat with aquatic grasslands of the Busanga plains (Now a Ramsar Site) offering rich feed, particularly Echinocloa spp.…”
Section: Discussionmentioning
confidence: 99%